Clinicopathological and prognostic value of epithelial cell adhesion molecule in solid tumours: a meta-analysis - Ding, Peiwen; Chen, Panyu; Ouyang, Jiqi; Li, Qiang; Li, Shijie (Frontiers in Oncology, 2023)
Background: Malignant tumors, mainly solid tumors, is a significant obstacle to the improvement of life expectancy at present. Epithelial cell adhesion molecule (EpCAM), a cancer stem cell biomarker, showed widespread expression in most normal epithelial cells and most cancers. Although the clinical significance of EpCAM in various malignant solid tumors has been studied extensively, the latent relationships between EpCAM and pathological and clinical characteristics in solid tumors and differences in the roles of EpCAM among tumors have not been clearly determined. The destination point of this study was to analyze the value of EpCAM in solid tumors in clinicopathological and prognostic dimension using a meta-analysis approach.A comprehensive and systematic search of the researches published up to March 7th, 2022 in PubMed, EMBASE, Web of Science, Cochrane library and PMC databases was performed. The relationships between EpCAM overexpression, clinicopathological characteristics, and survival outcomes were analyzed. Pooled hazard ratios (HRs) with 95% confidence intervals (CIs) and odds ratios (ORs) were estimated as indicators of the degree of correlation.This research was registed on PROSPERO (International prospective register of systematic reviews), ID: